KOMPETENSI ANDRAGOGI TUTOR DALAM PROSES PEMBELAJARAN PENDIDIKAN KESETARAAN PROGRAM PAKET C DI PKBM BINA KREASI KELURAHAN TANGKERANG TIMUR KECAMATAN TENAYAN RAYA PEKANBARU - Fiqi Rafika Nur’ain; Daeng Ayub Natuna; Wilson Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study reviewed the andragogy competence of tutors ineducational equality program C at PKBM Bina Kreasi Kelurahan Tangkerang TimurKecamatan Tenayan Raya Pekanbaru. The purpose of this research is to know thecompetency of the andragogy tutors at the community study center (PKBM) of a newpekanography creation. This type of research is a naturalistic descriptive approachwith a qualitative approach, the process of data collecting is conducted by interviewingthe three research subjects of 1 core informant and 2 control informants bydocumenting. In this study researchers used 3 subfoci from the focus of the competencyandragogy research tutors, which is: (1) the characteristics of citizens learn, (2)package curriculum c, (3) implementation of learning. The study of these three subfocusaims to know how well the andragogy of the tutor was at PKBM Bina Kreasi City ofPekanbaru.Key Words: Competency, Andragogy, Tutors